Advances in human aspects of road and rail transportation - Stanton, Neville 1960 (Advances in human factors and ergonomics series, 2013)
Human factors and ergonomics have made considerable contributions to the research, design, development, operation and analysis of transportation systems and their complementary infrastructure. This volume focuses on the causations of road accidents, the function and design of roads and signs, the design of automobiles, and the training of the driver. It covers accident analyses, air traffic control, control rooms, intelligent transportation systems, and new systems and technologies.